2014
DOI: 10.4085/090129
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Preceptors Serving in Dual Roles as Health Care Providers and Clinical Educators

Abstract: Context Preceptors play an integral role in training athletic training students (ATSs). Balancing roles as health care providers and educators can often be challenging. Role strain is a documented concern for the preceptor, yet limited information is available regarding other issues faced while supervising ATSs. Objective To explore preceptor challenges. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…4 Recent research suggests preceptors experience role strain because of the increased demands serving as a preceptor places on their time. 4,5 Providing preceptors with appropriate training and socialization into their roles may help mitigate some of that role strain. 4 Recently, Mazerolle et al 6 found preceptors are typically socialized into their roles through a combination of formal and informal processes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent research suggests preceptors experience role strain because of the increased demands serving as a preceptor places on their time. 4,5 Providing preceptors with appropriate training and socialization into their roles may help mitigate some of that role strain. 4 Recently, Mazerolle et al 6 found preceptors are typically socialized into their roles through a combination of formal and informal processes.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies that have focused on the experiences of preceptors are scarce, and the available research has mainly addressed the experiences of preceptors working with undergraduate nursing students (Dodge et al, 2014;Higgins et al, 2010;Muir et al, 2013;Omansky, 2010). The aim of this study is to explore the experiences of preceptors working with new nurses in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical expertise is often a key element to mentoring, 8 yet little data is available on the importance of experience and expertise and how they affect the mentoring received by students. The apprenticeship model for educational training, a model that is built upon the notion of mentoring and modeling best practices, is commonplace in healthcare programs (i.e., physical therapy, medical school, and others).…”
Section: Cultivating Symbiosis Of Preceptor-student Interactions In Cmentioning
confidence: 99%
“…11 Coupling the role as a preceptor with expectations that, as healthcare providers, preceptors must also (1) stay current in their practice, (2) continue to cultivate their clinical skills and competence, and (3) comply with additional responsibilities, can place a great deal of strain on preceptors to balance the various responsibilities. 8 This strain can be exacerbated because often the athletic trainer, who does not typically possess a background in pedagogy, is asked to provide instruction and feedback to the student. Developing an understanding for the role expectations as a preceptor is often completed through two means: formal and informal activities.…”
Section: Cultivating Symbiosis Of Preceptor-student Interactions In Cmentioning
confidence: 99%
See 1 more Smart Citation